PORTRAITS OF WRITERS OF DIFFERENT GENDER WHO FOCUS ON SOCIAL OPPRESSION IN THE NOVELS OF LIFE KITANDAWILI AND TEARS OF BLESSED - Jackline Njeri Murimi; Maingi Nkoroi Nancy (IJRDO- Journal of Educational Research, 2024)
In this study, we have examined how male and female writers highlight gender oppression in society by referring to the novels Chozi la Heri (Assumpta K. Matei) and Maisha Kitendawili (John Habwe). This study examines and analyzes on a gender basis how various characters are excluded and oppressed by society. In addition, the study has analyzed how those who are excluded and oppressed by society are portrayed in the eyes of male and female writers. In addition, suggestions for solving these problems have been suggested by referring to writers John Habwe and Assumpta K. Matei. It has been noted that John Habwe has portrayed the female gender as the most oppressed gender at the hands of the male unlike Assumpta Matei who has highlighted the male gender as a gender with many problems compared to the female gender. This study was guided by the Gender Theory, which was developed by feminist Elaine Showalter in 1840. This theory is used to analyze literary works written by authors of different genders. The data for this study was collected using three methods, namely library research where we read books, magazines, texts and newspapers to collect our data. We have also read various texts that focus on our topic, especially those written by both male and female genders about oppression. In addition, we have scoured the internet to understand more about the aspect of oppression in society. We have used purposive sampling in selecting the novels Maisha Kitendawili and Chozi la Heri. These two novels are written by male and female authors who are Swahili writers in Kenya. We collected our data from the novel Maisha Kitendawili and Chozi la Heri. In addition, we obtained our data from the internet, books, articles, libraries and dissertations. We analyzed our data using descriptive and numerical data, descriptions and explanations to present the data. This data helped us to assess whether male and female writers address issues of oppression in the same or different ways. This study is intended to be useful for the literary scholar in gaining knowledge and experience of criticism about the marginalized community and to understand in depth the various works that address the advocacy of various genders who are marginalized in society. This work also helps us in highlighting and clarifying how female and male writers contribute to addressing issues of oppression of various genders and issues concerning the society in which we live. In addition, this study contributes to providing solutions to various ways of addressing the issue of oppression of various genders.